Bio-larvicidal Potential of Betel Leaves (Piper betle L) Ethanolic Extract in Addition of PEG 400 Diluent on Aedes aegypti Larvae - Dewi, Listiana Masyita; Ariffah, Hilda Zaniba; Aisyah, Riandini; Nurhayani, Nurhayani (Biology, Medicine, & Natural Product Chemistry, 2023)
Dengue hemorrhagic fever (DHF) is a kind of vector transmitted disease, by Aedes aegypti. It is one of major public health problem around the world, including Indonesia, because it may lead to epidemics and death in a short time. The use of plant extracts as bio-larvicidal is thought to be a promising solution, and one of them is the betel leaves (Piper betle L). The addition of polyethylene glycol (PEG) as a diluent is thought may increase the dispersity of plant extract in the water which is larval medium of growth. Objectives: To determine the bio-larvicidal potential of 95% ethanolic extract of betel leaves (EEBL) in addition of PEG 400 diluent on the Aedes aegypti larval mortality. Material and Method: Betel leaves were extracted by maceration using 95% of ethanol. There are two kinds of EEBL concentration used, 0.2% dan 0.4%. PEG 400 was also added as diluent. The samples in this study were Aedes aegypti larvae at instar III-IV, with a total of 400 larvae. Evaluation was performed at 6, 12, 18, and 24 hours. The data obtained was then analyzed by Kruskall Wallis test and post-hoc Mann Whitney test. Result: In all of treatment groups, larval mortality was reached 100% at 24 hours. From the Kruskall Wallis test, p-value obtained was <0.05. From post-hoc Mann Whitney test, the p-value obtained in the comparation between treatment groups and positive control group was >0.05, and the p-value obtained in the comparation between treatment groups and negative control group was <0.05. Conclusion: EEBL in addition of PEG 400 diluent is potential as bio-larvicidal on Aedes aegypti larvae. It is also known that EEBL at concentration of 0.2% and 0.4% in addition of PEG 400 are as effective as temephos as larvicides on Aedes aegypti larvae.